UMP won gold medals and Special Awards In EUROINVENT 2012 - UMP, PNC
Universiti Malaysia Pahang (UMP) did very well at an international competition when four of its undergraduates garnered three gold medals and a silver medal as well as grabbing home all the special awards in the European Exhibition of Creativity and Innovation 2012 (EUROINVENT) in Romania on May 12, 2012.